Environmental, economic and social trade-offs of membrane-based direct air capture technologies integrated with CO2 conversion using life cycle assessment - Tianhui Fan; Siyu Shen; Chun Yat (Benjamin) Sit; Paul J.A. Kenis; Andrew Chapman (Journal of CO2 Utilization)
Technological solutions to address climate change are coalescing around renewable energy deployment. Yet, the deployment of renewables alone may not be sufficient to restrict temperature increases in line with Paris Agreement targets. The emergence of carbon negative technologies to bridge this shortfall is needed and expected to overcome this gap. Among these technologies, direct air capture (DAC) is being deployed at multiple scales using various approaches. This study investigates membrane-based DAC integrated with subsequent carbon dioxide to carbon fuel conversion, i.e., DAC with utilization (DAC-U). The DAC-U evaluation is undertaken holistically, beginning with a cradle-to-grave life cycle assessment, followed by economic feasibility scenario analysis and social acceptability analysis to establish acceptable deployment pricing and necessary policy interventions. This study reveals that, although the DAC-U represents a carbon negative capable technology with positive lifestyle and environmental outcomes, high capital costs present a significant barrier to deployment. To overcome this barrier, a robust policy regime including subsidies or fuel credits may be necessary. Further technological innovation and efficiency gains will also close this gap, meaning that the membrane-based DAC-U concept may play a role in achieving carbon neutrality goals in the near future.